Managing parasport: An investigation of sport policy factors and stakeholders influencing para-athletes' career pathways. Issue 5 (November 2020) - Patatas, Jacqueline Martins; De Bosscher, Veerle; Derom, Inge; De Rycke, Jens
Highlights: Stakeholders involved in policy processes need to critically position disability in order to develop para-athletes' pathways. Support services provided to para-athletes need to be tailormade to each disability group and sport classification. Need to revisit the level of education, qualification, and investments that coaches receive to deliver optimal para-athletes' pathways. Abstract: The way disability is understood and positioned by key stakeholders informs how policies are implemented in the development of pathways to sporting excellence of an athlete with a disability. In this paper, the authors seek to identify which sports policy factors and stakeholders influence the development of athletic career pathways in Paralympic sport (i.e., attraction, retention, competition, talent identification and development, elite, and retirement phases). Drawing from the theories of disability and the literature on elite sport policy, an interview protocol on policy dimensions and principles to support para-athletes' development was created, and 32 key stakeholders from the Brazilian Paralympic sport context were interviewed. The data revealed that coaching provision and education as a policy factor and coaches with disability-specific knowledge as a stakeholder were perceived as most influential during all the phases of para-athletes' careers. The classification system emerged as a parasport-specific factor that can facilitate or inhibit the development of para-athletes' careers, influencing the implementation of policies. The authors suggest that understanding the concept of disability is notably essential when stakeholders have to think strategically and adapt management principles from able-bodied sporting contexts. Therefore, critically positioning disability within policy decision making can improve the thinking, action, and behaviour of policymakers, coaches, and sports managers, leading to the more efficient delivery of successful para-athletes' careers.